The Hermeneutics of Gadamer and the practice of Environmental Education - Schmitt, Lilian Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article aims to enable reflections on relations between the Hermeneutics, as a philosophical branch, and the environmentally oriented educational practice. To achieve this goal, will be addressed on the Philosophical Hermeneutics from Hans-Georg Gadamer's ideas, that with the work entitled Truth and Method, considered a milestone in twentiethcentury thought, influenced different modern scientific areas. Given that the field of Environmental Education, being still na emerging field, is in a moment of theoretical consolidation, it is understood that Hermeneutics can contribute as much as theoretical foundation and as approach in daily practice to environmental education.